2019
DOI: 10.1002/ese3.326
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between coal and gas outburst risk and adsorption properties of coal seams

Abstract: Based on the Langmuir adsorption model, the adsorption constants of eighteen coal samples from the same coal mine with outburst risk, weak outburst risk, and non‐outburst risk were tested by high‐pressure capacity method under different temperature conditions. The results show that the adsorption constants a and b monotonically decrease with the increase in temperature. The relationship between a and temperature shows three stages: accelerated decreasing stage, decelerated decreasing stage, and stable stage. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Therefore, a large number of tunnels and chambers will be constructed and excavated in deep rockmass to meet the needs of underground engineering projects (Dammyr et al;Huang et al; Kang et al). Compared to the stress states of shallow buried depth, the mechanical characteristics of hard and brittle rocks at greater depth have been acknowledged to behave quite differently because of their complex stress states . Because a large amount of energy is stored in the hard rockmass, the excavation unloading of deep tunnels and chambers will lead to stress redistribution and concentration, which create favorable conditions for rock fracturing and instability .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a large number of tunnels and chambers will be constructed and excavated in deep rockmass to meet the needs of underground engineering projects (Dammyr et al;Huang et al; Kang et al). Compared to the stress states of shallow buried depth, the mechanical characteristics of hard and brittle rocks at greater depth have been acknowledged to behave quite differently because of their complex stress states . Because a large amount of energy is stored in the hard rockmass, the excavation unloading of deep tunnels and chambers will lead to stress redistribution and concentration, which create favorable conditions for rock fracturing and instability .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the stress states of shallow buried depth, the mechanical characteristics of hard and brittle rocks at greater depth have been acknowledged to behave quite differently because of their complex stress states . Because a large amount of energy is stored in the hard rockmass, the excavation unloading of deep tunnels and chambers will lead to stress redistribution and concentration, which create favorable conditions for rock fracturing and instability . In situ measurements have shown extremely unconventional failure phenomena in deep mining and tunneling engineering such as slabbing, zonal disintegration, and rockburst, which are of great threats to safe and efficient underground construction and activity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coal and gas outbursts are complex dynamic disasters, which, based on a comprehensive supposition, result from interactions among the structural mechanical properties of coal, ground stress, and gas pressure . In addition, coal and gas outbursts are closely related to geological structure, adsorption characteristics, and other factors . Through protracted and unremitting efforts, researchers from several countries have advanced various outburst prediction methods based on the understanding of outburst mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 As the permeability is often very low for complex coal structures, hydraulic methods that enable an increase in the water content and thus reduce the gas pressure of coal seams, including coal seam water injection, 17 hydraulic punching, and hydraulic extrusion, are the main techniques used to improve permeability before coal mining. [18][19][20] Field tests have shown that the gas emission from coal increases during the water injection process 18,[21][22][23] ; in contrast, experimental results have shown that an increase in the moisture content of coal has a significant inhibitory desorption effect on the adsorbed gas. 24,25 Thus, it is necessary to determine the influence of external water on the desorption character of the adsorbed coalbed methane in coal.…”
Section: Introductionmentioning
confidence: 99%